2022
DOI: 10.1002/anie.202202542
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Axially Chiral Styrene‐Carboxylic Esters by Rhodium‐Catalyzed Chelation‐Controlled [2+2+2] Cycloaddition

Abstract: Axially chiral styrene‐carboxylic esters were synthesized in high yields with excellent enantioselectivity by the cationic rhodium(I)/H8‐BINAP complex‐catalyzed chelation‐controlled [2+2+2] cycloaddition reactions of 1,6‐ and 1,7‐diynes with 1,3‐enyne‐carboxylic esters. The diastereo‐ and enantioselective synthesis of C2 symmetric axially chiral cis and trans‐stilbene‐dicarboxylic esters was also achieved by the double [2+2+2] cycloaddition reactions of two molecules of the 1,6‐diyne with 2,3‐dialkynylmaleate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…On the basis of these results, a plausible mechanism for the three-component [2+2+2] cycloaddition is shown in Scheme 5b. [15][16][17] Terminal alkynes 1 a and 1 g and enamide 2 d react with the cationic rhodium to give enamide-…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of these results, a plausible mechanism for the three-component [2+2+2] cycloaddition is shown in Scheme 5b. [15][16][17] Terminal alkynes 1 a and 1 g and enamide 2 d react with the cationic rhodium to give enamide-…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the RhCl­(PPh 3 ) 3 catalyst, our research group has reported that cationic Rh­(I)/biaryl bisphosphine complexes are highly effective catalysts for the [2 + 2 + 2] cycloadditions of 1,6-diynes with alkynes, nitriles, and isocyanates under mild conditions. Here we report the cationic Rh­(I)/H 8 -BINAP complex-catalyzed [2 + 2 + 2] cycloaddition using 1,8-dialkynylnaphthalenes, giving substituted fluoranthenes and azafluoranthenes at room temperature (Figure c, below).…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalyzed [2+2+2] cycloaddition of three 2π components has attracted much attention, due to its high efficiency and atom economy for the rapid construction of functionalized sixmembered carbo-and heterocycles with high functional group tolerance (1)(2)(3). In particular, transition metal-catalyzed inter-and intramolecular asymmetric [2+2+2] cycloadditions of alkynes have been proven as a powerful tool to synthesize valuable benzenebased skeletons bearing central (4,5), axial (6)(7)(8)(9), planar (10,11), helical chirality (12)(13)(14)(15)(16), and chiral belts (17)(18)(19), which were well established by Tanaka and others (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%